Engineering Polar Oxynitrides: Hexagonal Perovskite BaWON2. (18th August 2020) - Oró‐Solé, Judith; Fina, Ignasi; Frontera, Carlos; Gàzquez, Jaume; Ritter, Clemens; Cunquero, Marina; Loza‐Alvarez, Pablo; Conejeros, Sergio; Alemany, Pere; Canadell, Enric; Fontcuberta, Josep; Fuertes, Amparo
Abstract: Non‐centrosymmetric polar compounds have important technological properties. Reported perovskite oxynitrides show centrosymmetric structures, and for some of them high permittivities have been observed and ascribed to local dipoles induced by partial order of nitride and oxide. Reported here is the first hexagonal perovskite oxynitride BaWON2, which shows a polar 6H polytype. Synchrotron X‐ray and neutron powder diffraction, and annular bright‐field in scanning transmission electron microscopy indicate that it crystalizes in the non‐centrosymmetric space group P63 mc, with a total order of nitride and oxide at two distinct coordination environments in cubic and hexagonal packed BaX3 layers. A synergetic second‐order Jahn–Teller effect, supported by first principle calculations, anion order, and electrostatic repulsions between W 6+ cations, induce large distortions at two inequivalent face‐sharing octahedra that lead to long‐range ordered dipoles and spontaneous polarization along the c axis. The new oxynitride is a semiconductor with a band gap of 1.1 eV and a large permittivity. Abstract : The new 6H hexagonal perovskite oxynitride BaWON2 is a non‐centrosymmetric polar compound that shows a total order of nitrogen and oxygen in two distinct coordination environments. The combination of anion order, electrostatic repulsion between W 6+ cations, and a second‐order Jahn–Teller effect induce different distortions at three inequivalent tungsten octahedra, leading to long‐range ordered dipoles and spontaneous polarization along the c axis.